2D hetero-nanosheets to enable ultralow thermal conductivity by all scale phonon scattering for highly thermoelectric performance. (December 2016) - Li, Shuankui; Xin, Chao; Liu, Xuerui; Feng, Yancong; Liu, Yidong; Zheng, Jiaxin; Liu, Fusheng; Huang, Qingzhen; Qiu, Yiming; He, Jiaqing; Luo, Jun; Pan, Feng
Abstract: It remains a great challenge to design thermoelectric materials with high figure of merit ZT because of the strongly correlated material parameters such as the electrical conductivity, thermal conductivity, and Seebeck coefficient, which restricts the maximum ZT values to ~1 in bulk thermoelectric materials. Here, we demonstrate a strategy based on nanostructuring and alloying to synthesize the two-dimensional (2D) Bi2 Te2.7 S0.3 /Bi2 Te3 hetero-nanosheet with atomically thin heterojunction interfaces to optimize the electron and phonon transport behavior. A full-spectrum phonons scattering has been achieved to enable ultralow thermal conductivity by the atomic-scale alloy and defect to target high frequency phonons, heterojunction interface to target mid-frequency phonons, and nanoscale grains boundary to target low-frequency phonons. With this technique, the lattice thermal conductivity (κlatt ) is dramatically reduced to 0.2-0.3 W m −1  K −1 near the lower limit of the randomly oriented κlatt (0.18 W m −1  K −1 ), but the electrical transport properties is well maintained. Taking advantage of the maximumly reduced thermal conductivity as well as the maintained power factors, the maximum ZT reaches 1.17 and 0.9 at 450 K and around room temperature, respectively, approximately three times higher than their counterparts without atomically thin heterostructure. Graphical abstract: Highlights: The two-dimensional (2D) Bi2 Te2.7 Se0.3 /Bi2 Te3 hetero-nanosheet with atomically thin heterojunction interfaces has been prepared. A full-spectrum phonons scattering has been achieved to enable ultralow thermal conductivity. Taking advantage of the maximumly reduced thermal conductivity as well as the maintained power factors, the maximum ZT reaches 1.17 at 450 K.